Evaluating the impact of social and behavior change communication intervention on improving documentation practices among healthcare workers in southern Nigeria: a before and after study - Eze, Chinwe; Murphy-Okpala, Ngozi; Ezeakile, Okechukwu; Chukwu, Joseph; Ekeke, Ngozi; Agu, Chibuike; Ezenwosu, Ifeyinwa; Matiku, Sode; Kirubi, Beatrice; Meka, Anthony; Njoku, Martin; Iyama, Francis S.; et al. (Frontiers in Public Health, 2025)
BackgroundProper documentation is very essential to healthcare practice. It is vital for continuity of care and communication among healthcare workers. This study was designed to determine the effectiveness of the application of Social and Behavioral Change Communication strategy to improving documentation practices among healthcare workers in two states in Nigeria.MethodsA longitudinal study with a pre-post-intervention design was utilized. An audit of documented specimen examination request forms was conducted at two-month intervals. The initial audit served as baseline. Subsequent audits were to monitor progress and assess impact of intervention. For each audit, a minimum of 10 facilities was purposively selected across the two states, including an average of five GeneXpert sites and six health facilities. Based on availability, a maximum of 50 specimen examination request forms were consecutively selected per GeneXpert site or facility for audit. The interventions included modification of the specimen examination request form, training and educational sessions, regular audit of forms, progress monitoring, and feedback.ResultsThere was an increase in the proportion of each variable meeting the documentation standard across the four audit rounds. This progress was observed across the four audit rounds for most of the variables, with the most substantial improvement recorded in the fourth audit. In all, there was a significant improvement in the proportion of each specimen examination form that met the documentation standards (p < 0.001). These variables included detailed address of patient, patient phone number and phone number of person requesting the examination. Variables on the revised form which showed significant changes across the four audit periods included name and phone number of next of kin (p < 0.001).ConclusionThe SBCC intervention markedly enhanced accurate and comprehensive documentation of specimen examination request forms among frontline healthcare workers. Key components, such as repeated training sessions, education emphasizing the benefits of sound documentation practices, consistent supervision, monitoring, feedback, and ensuring a sufficient supply of forms, collectively played integral roles in maximizing the effectiveness of the intervention.